2022
DOI: 10.1093/eurheartj/ehac109
|View full text |Cite
|
Sign up to set email alerts
|

Circadian nuclear receptor Rev-erbα is expressed by platelets and potentiates platelet activation and thrombus formation

Abstract: Aims Adverse cardiovascular events have day/night patterns with peaks in the morning, potentially related to endogenous circadian clock control of platelet activation. Circadian nuclear receptor Rev-erbα is an essential and negative component of the circadian clock. To date, the expression profile and biological function of Rev-erbα in platelets have never been reported. Methods and results Here, we report the presence and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The identification of NR1D1 as a novel functional receptor in mitochondrial metabolism regulation in vascular cells might broaden our understanding of the multiple biological functions of NR1D1. 38 Our observations, along with recent findings about the role of NR1D1 in cardiovascular tissues from several research groups, 8 , 9 , 12 , 50 provide support for NR1D1 as an essential regulator of cardiovascular biology. It is important that our study unveils a previously undescribed NR1D1-ACO2-αKG axis in regulating mitochondrial metabolism, and provides proof-of-concept evidence indicating the therapeutic value of αKG supplementation in AAA prevention and treatment.…”
Section: Clinical Implications Of This Studysupporting
confidence: 74%
See 2 more Smart Citations
“…The identification of NR1D1 as a novel functional receptor in mitochondrial metabolism regulation in vascular cells might broaden our understanding of the multiple biological functions of NR1D1. 38 Our observations, along with recent findings about the role of NR1D1 in cardiovascular tissues from several research groups, 8 , 9 , 12 , 50 provide support for NR1D1 as an essential regulator of cardiovascular biology. It is important that our study unveils a previously undescribed NR1D1-ACO2-αKG axis in regulating mitochondrial metabolism, and provides proof-of-concept evidence indicating the therapeutic value of αKG supplementation in AAA prevention and treatment.…”
Section: Clinical Implications Of This Studysupporting
confidence: 74%
“… 37 , 38 It is important that emerging evidence has shown that NR1D1 regulates cardiovascular physiology/pathology. 8 , 9 , 13 Although NR1D1 has been reported to inhibit atherosclerotic development, 13 we unexpectedly found a profound detrimental effect of NR1D1 on AAA development. NR1D1 was upregulated in human and MASMCs from AAA tissues, with its gene expression ranked the highest in fold change among all 49 NRs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It is now long known that acute myocardial infarctions occur more frequently in the morning [ 75 ]. This correlates with a peak in platelet activation during the morning, associated with the expression of REV-ERBα in platelets [ 76 ]. Anti-aggregative drugs such as acetylsalicylic acid (ASA) are therefore used for secondary prevention of coronary artery disease.…”
Section: Circadian Medicine and Chronopharmacotherapymentioning
confidence: 99%
“…How does GPR35 promote neutrophil adhesion with platelets? We suspect that GPR35 is involved in the receptor-induced neutrophil shape change and promotes the cytoskeleton remodeling of neutrophils through G12/G13-mediated or Gai-mediated Rho/Rho kinase-dependent ERM (ezrin/radixin/moesin) phosphorylation regulation [ 7 , 8 ] . We believe that there is a close relationship between platelet activation and neutrophil recruitment.…”
mentioning
confidence: 99%